(untitled) (Texas Journal of Agriculture and Biological Sciences, 2024)
This article talks about the importance of magnolia sapling in greening the Shahrisabz region. Relying on scientific data, the author studied and analyzed the specific aspects of the importance of magnolia in the greening of the Shahrisabz region on the basis of existing biological literature.